The Relationship Between Knowledge and Education Levels of Pregnant Women and the Regularity of Antenatal Care Visits at Tigapanah Community Health Center in 2024 - Alfri Yoganta Sembiring; Maestro Simanjuntak; Juli Jamnasi (Universitas Methodist Indonesia, 2024)
Background: Maternal and prenatal mortality remain serious healthissues, primarily due to behaviors and a lack of understanding regardinghealthcare, particularly Antenatal Care (ANC). The irregularity inprenatal check-ups is influenced by factors such as the educational leveland knowledge of pregnant women.Objective: To analyze the relationship between knowledge and educationallevel of pregnant women with the regularity of prenatal check-ups atTigapanah Health Center.Methods: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 77 pregnant women selectedthrough purposive sampling. Data were collected using a validated andreliable questionnaire, and analyzed using the Chi-Square statistical test.Results: The results from a total of 77 samples indicate a significantrelationship between knowledge and the regularity of prenatal check-ups(p = 0.002). The educational level also showed a significant relationshipwith the regularity of prenatal check-ups (p = 0.001).Conclusion: There is a significant relationship between knowledge andeducational level with the regularity of prenatal check-ups.Keywords: Knowledge, Educational Level, Pregnant Women, Regularityof Prenatal Check-Ups, ANC